2014
DOI: 10.1073/pnas.1318688111
|View full text |Cite
|
Sign up to set email alerts
|

Critical role for inflammasome-independent IL-1β production in osteomyelitis

Abstract: The immune system plays an important role in the pathophysiology of many acute and chronic bone disorders, but the specific inflammatory networks that regulate individual bone disorders remain to be elucidated. Here, we characterized the osteoimmunological underpinnings of osteolytic bone disease in Pstpip2 cmo mice. These mice carry a homozygous L98P missense mutation in the Pombe Cdc15 homology family phosphatase PSTPIP2 that is responsible for the development of a persistent autoinflammatory disease resembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
122
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(128 citation statements)
references
References 34 publications
4
122
0
Order By: Relevance
“…Because recent reports showed that IL-1b and inflammasomeactivated caspases are critical for the disease development in CMO mice (35)(36)(37), we decided to analyze the silica-triggered IL-1b production in more detail, especially with respect to the interactions among PSTPIP2, SHIP1, and Csk described earlier. To address the question of PSTPIP2 phosphorylation under these conditions, we performed the immunoprecipitation of endogenous PSTPIP2 from unstimulated or LPS-primed and silica-stimulated BM cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because recent reports showed that IL-1b and inflammasomeactivated caspases are critical for the disease development in CMO mice (35)(36)(37), we decided to analyze the silica-triggered IL-1b production in more detail, especially with respect to the interactions among PSTPIP2, SHIP1, and Csk described earlier. To address the question of PSTPIP2 phosphorylation under these conditions, we performed the immunoprecipitation of endogenous PSTPIP2 from unstimulated or LPS-primed and silica-stimulated BM cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, more recent work has suggested that neutrophils may also be a critical cell type in disease initiation (35,36). Similar to several other autoinflammatory syndromes, the disease appears to be, at least in part, caused by the enhanced production of IL-1b (35,37). The molecular mechanism of how PSTPIP2 prevents autoinflammatory disease development remains largely unknown.…”
mentioning
confidence: 99%
“…5 Both IL-1a and IL-1b are capable of instigating sterile inflammation and we previously have shown that these cytokines drive distinct neutrophilmediated autoinflammatory disorders. 10,34 Although a reason for this specificity currently is unknown, a possible reason could be the nature of cell death perturbed in each autoinflammatory disorder. 9 Although necrotic cell death releases bioactive IL-1a, IL-1b requires caspase-1e and/or caspase-8emediated maturation and release.…”
Section: Discussionmentioning
confidence: 99%
“…Mice harboring a spontaneous missense mutation in the proline-serine-threonine phosphatase-interacting protein 2 (Pstpip2) gene, which abolishes protein expression, develop a phenotype reminiscent of CRMO, with enhanced osteoclastogenesis and bone resorption (137). These mutant mice overproduce IL-1β due to combined and redundant actions of the NLRP3 inflammasome and caspase 8 (138)(139)(140), suggesting that inflammasome-independent IL-1β release may occur in some situations.…”
Section: Foxp3mentioning
confidence: 99%